Arm-Trunk Coordination during Virtual Reality Training. - Ongolo Zogo, Clémence; Legendre, Martin; Robb, Trevor; Sheehy, Lisa (Université d'Ottawa | University of Ottawa, 2016)
Virtual reality training (VRT) performed while sitting can be used to challenge sitting balance and upper extremity reaching movements during stroke rehabilitation. However, the extent to which trunk forward lean compensates for upper extremity reaching movements during VRT is uncertain. The objectives of this cross-sectional observational study are to determine how much trunk compensation occurs in younger and older healthy adults and stroke survivors during VRT, and to compare the degree of trunk compensation in two levels of the same game, across the different groups. Reflective markers are attached to the shoulder, elbow, index finger and wrist of both arms, to the trunk and forehead of two healthy younger and two older adults, and two stroke survivor participants. A Vicon motion capture system is used to track the markers while participants perform three VRT games, each at two levels of difficulty in restrained and unrestrained conditions. The games encourage reaching movements in central, ipsilateral and contralateral arm workspaces. Data collected on the hand path and range of anterior-posterior trunk movement will be analyzed to quantify the degree of trunk compensation, which will be compared between participant groups for each game. Evaluating trunk compensation during VRT will guide rehabilitation professionals in their choice of games to achieve their treatment goals for their stroke patients.